DERECHOS HUMANOS Y POLÍTICAS SOCIALES EN MIGRACIÓN. APUNTES NODALES - Flores Martínez, Rosa María (UNIVERSIDAD DE SONORA, 2023)
Abstract In recent decades, migratory flows have been increasing, the exodus occurs especially in regions with less development. Likewise, the conditions and problems faced by migrants before, during and after mobility have become more complex and diversified, exposing those who transit to situations of human rights violations. Therefore, the objective of this is to analyze from the socio-legal framework, social policies aimed at the protection of migrants. Based on the documentary methodology, instruments and regulations are explored at the international and national level, as well as social policies as mechanisms of social intervention of the State. The results show that, even though there is a wide socio-legal scaffolding, whose articulating axis is the protection and guarantee of the human rights of migrants; in practice, intervention towards the migrant subject continues to be influenced by notions of social exclusion. Therefore, it is proposed to rethink social praxis, from a perspective of recognition of migrants as political agents and subjects of rights, where social justice and equity are the dimensions that sustain such interventions.